THEME AND RHEME IN PETERPAN NOVEL - Anggita Hermayenti , Diani Syahputri, Yunita Mutiara Harahap (EXCELLENCE: Journal of English and English Education, 2021)
This study deals with the Theme and Rheme in Peterpan novel. The objective of this study was to find out the kinds and the dominant kind of Theme and Rheme in Peterpan novel. This study was conducted by applying descriptive qualitative research design. The data of this study were taken from Peterpan novel chapter I until chapter XVII. It was found that there were 6 kinds of Theme and Rheme in this study, namely: Simple Theme was 11 clauses or 16.41%, Multiple Theme was 9 clauses or 13.43%, Unmarked Simple Theme was 17 clauses or 25.37%, Unmarked Multiple Theme was 18 clauses or 26.86%, Marked Simple Theme was 2 clauses or 2.98%, and Marked Multiple Theme was 10 clauses or 14.92%. It meant that Unmarked Multiple Theme was the dominant kind in this study because Unmarked Multiple Theme was easier to search in each clause and can be understood by the readers.